Facile carbon fiber-sewed high areal density electrode for lithium sulfur batteries. Issue 73 (13th August 2020) - He, Mengxue; Li, Yaqi; Liu, Songsong; Guo, Rui; Ma, Yulin; Xie, Jingying; Huo, Hua; Cheng, Xinqun; Yin, Geping; Zuo, Pengjian
Abstract : Carbon fiber-sewed electrode with sulfur loading over 10 mg cm −2 is achieved via typical coating method. Abstract : A high sulfur loading cathode strengthened by using carbon fiber (CF) is achieved via a typical coating method. Interlaced fibers and abundant hairline cracks ensure an unobstructed electron transfer path and sufficient Li-ion transport channels. The CF-sewed electrode with sulfur loading up to 10 mg cm −2 delivers a high areal capacity of over 7 mA h cm −2 after 96 cycles with a high coulombic efficiency over 99%.